Focal Choroidal Elevations: Localized Pigment Epithelial Contour Alterations due to Isolated Choroidal Vessels - Rachel L. Chu; Nicole A. Pannullo; Eric J. Sigler (Journal of Ophthalmology)
Purpose. The objective of this case series was to describe the clinical and imaging features of focal choroidal elevations (FCE), which are chorioretinal contour changes induced by individual choroidal vessels within an overall thin-appearing choroid. Methods. A total of 787 enhanced depth imaging (EDI) spectral domain optical coherence tomography (SD-OCT) patient images were initially screened for the presence of FCE. Prospective imaging analysis of 38 patients with FCE was done. Mean central macular choroidal thickness (CMCT), FCE location, FCE vessel lumen diameter, patient demographics, cycloplegic autorefraction, ophthalmoscopic findings, and presence of choroidal neovascularization (CNV) in the fellow eye were recorded. Results. FCE were observed in 25 patients with age-related macular degeneration (ARMD), in 5 patients with high myopia, and in 8 patients with age-related choroidal atrophy (ARCA). Mean patient age was 80 ± 9.4 years. Mean CMCT was 86 ± 40 μm. Mean lumen diameter of the vessels inducing FCE was 131 ± 33 μm. Conclusions. FCE are relatively frequently encountered morphologic features of elderly patients with ARMD, high myopia, and ARCA, and have a distinct clinical and imaging morphology which differs from classically described chorioretinal folds. The lesions may commonly be mistaken for pigment epithelial detachments on ophthalmoscopy, may be associated with CNV in fellow eyes, and have a characteristic SD-OCT appearance.